1998
DOI: 10.1108/10662249810211638
|View full text |Cite
|
Sign up to set email alerts
|

A framework for effective commercial Web application development

Abstract: The World Wide Web (WWW) or the Web has been recognized as a powerful new information exchange channel in recent years. Today, an ever-increasing number of businesses have set up Web sites to publicize their products and services. However, careful planning and preparation is needed to achieve the intended purpose of this new information exchange channel. This paper proposes a comprehensive framework for effective commercial Web application development based on prior research in hypermedia and humancomputer int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(60 citation statements)
references
References 9 publications
0
53
0
5
Order By: Relevance
“…A qualified and well-performing hotel website should be efficient, informative, and user friendly (Jeong & Lambert, 2001). Thus, the usefulness of hotel websites is gauged by the effectiveness of their performance in terms of functionality and usability (Lu & Yeung, 1998). Bai, Law, and Wen (2008) reported that customer satisfaction can be influenced by website functionality and usability, which consequently affect purchase intention.…”
Section: Quality Of Hotel Websitesmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualified and well-performing hotel website should be efficient, informative, and user friendly (Jeong & Lambert, 2001). Thus, the usefulness of hotel websites is gauged by the effectiveness of their performance in terms of functionality and usability (Lu & Yeung, 1998). Bai, Law, and Wen (2008) reported that customer satisfaction can be influenced by website functionality and usability, which consequently affect purchase intention.…”
Section: Quality Of Hotel Websitesmentioning
confidence: 99%
“…Consumer's needs and requirements on a website are often determined by website evaluation, which is the most frequently used method to reflect the website performance (Lu & Yeung, 1998;Faba-Perez & Moya-Anegon, 2005). Most of the website evaluation studies focused on developing new evaluation methods or modified the existing websites using various frameworks (Law, Qi, & Buhalis, 2010).…”
Section: Perceived Hotel Website Performance From Consumer Perceptionsmentioning
confidence: 99%
“…It is believed that many companies must be in the situation that they have paid for a web site but it is never visited or does not seem to attract any customers and draw the conclusion that the Internet is not useful for them. In fact creating an effective web site needs to be taken seriously in the face of all the competition already on the Internet (Lu and Yeung, 1998). It is first and foremost a marketing task (Angelides, 1997;Dholakia and Rego, 1998;Saaksjarvi, 1999) and should not be left to computing professionals.…”
Section: Introductionmentioning
confidence: 99%
“…The relevant literature suggests several different quality indicators (Fredin, 1997;Just, et al, 1997;Day, 1997;Schneiderman, 1997;Buchanan and Lukaszewski, 1997;Fredin and David, 1998;Lu and Yeung, 1998;. We selected 10 of these indicators.…”
Section: Political Party Websites and Their Effectivenessmentioning
confidence: 99%